Online Single Submission Sebagai Strategi Penertiban Administrasi Perizinan Berusaha di Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu Kota Denpasar - Dewi, Putu Indah Kresna; Wijaya, Komang Adi Sastra; Purnamaningsih, Putu Eka (CITIZEN CHARTER, 2022)
This research aimed to find out how the application of Online Single Submission as a strategy for controlling business licensing administration at Investment and One Stop Integrated Service Department (DPMPTSP) of Denpasar City. With descriptive qualitative research methods, strategic management theory from Wheelen and Hunger (2012) is used with indicators environment analyses strategy formulation, strategy implementation, also evaluation and control. Based on the result of each indicator, the main strategy that DPMPSTP of Denpasar City applied are adapting the Online Single Submission system, improves the quality and quantity of employees, maximizes socialization, and publishes supporting programs. In its implementation, Online Single Submission system has proven to be progressively successful in streamlining the flow of licensing services that make it easier for the public, provide transparency over time and costs, and increase the amount of investment in Denpasar City. Keywords: Online Single Submission, Administration, Business License, Strategic Management